(untitled) - Suzuki, Daisetz T. (Princeton, N.J., 1959)
General remarks on Japanese art culture; Zen and study of Confucianism; Zen and the samurai; Zen and swordsmanship I; Zen and swordsmanship II;...
Keywords: Zen Buddhism,Thiền Phật giáo; History,Lịch sử; Japan,Nhật Bản